The Nexus Between Blue Economy and Sustainable Development: A Systematic Literature Review and Mapping Study - Aprizal, Anggi; Wiranatakusuma, Dimas Bagus; Razak, Dzuljastri Abdul (Journal of Economics Research and Social Sciences, 2025)
This study investigates the relationship between the blue economy and sustainable development through a mapping study and systematic literature review (SLR) adhering to the PRISMA framework. An examination of 57 Scopus-indexed journal papers indicates a robust correlation between the blue economy and sustainability, highlighting significant developing topics such as innovation, the doughnut economy, environmental legislation, regenerative systems, digitization, and Sustainable Development Goals (SDGs). Prominent themes encompass the blue economy, sustainability, ocean economy, innovation, small-scale fisheries, blue equity, Sustainable Development Goals (SDGs), and fisheries. In contrast, underexamined yet promising subjects include economic growth, ocean sustainability, alternative livelihoods, deep-sea mining, aquaculture, tourism, and environmental law. The intersection of Blue Economy and Sustainable Development emphasizes Strategic Management and Marine and Coastal Tourism as the principal focus (21.05%), succeeded by Ocean Governance and Marine Spatial Planning, Sustainable Aquaculture, Marine Food Production and Blue Energy Innovation, and Climate Change, Risk and Conservation (17.54%). Fisher Support (12.28%) prioritizes fisher welfare, whilst Marine Cultural Heritage and Social Dimensions (10.53%) underscore social and cultural significance. This study delineates research trends, analyzes deficiencies, and provides policymakers, scholars, and practitioners insights to promote sustainable marine-based economic development. This study enhances the comprehension of the relationship between the Blue Economy and Sustainable Development by delineating research trends, pinpointing knowledge deficiencies, and emphasizing critical topic areas like strategic management, marine governance, sustainable aquaculture, and assistance for fishers. The results highlight the interdisciplinary aspect of this connection, especially in incorporating innovation, digitalization, and doughnut economy ideas into marine economic policies. The study's implications are relevant to academia, politicians, and practitioners, offering a basis for future research on emergent topics such as deep-sea mining, blue growth, and climate risk reduction. Enhancing marine spatial planning, fisher welfare, and socio-cultural aspects can promote inclusive and sustainable marine development, assuring ecological resilience and advancing economic fairness for coastal communities.